A Brief Sketch of the Possibility of a Hegelian Cosmopolitanism. Issue 1 (February 2016) - Rose, David Edward
Abstract : The following paper investigates the possibility of an account of cosmopolitan thought inspired by Hegel's treatment of Kant's ethical theory and his associated social concept of recognition. Cosmopolitanism requires the agent to recognize themself as a global agent participating in a shared community, but conventional political strategies do not possess the resources to satisfy this demand for self-understanding. Such a self-understanding is enabled by the objective freedom of a common shared humanity grounded in rational self-determination. The paper shows that it is possible to extrapolate Hegel's outline of the state in the Philosophy of Right (perhaps contrary to Hegel's own intuitions) to describe a global community coherent with such a subject.